EFEKTIFITAS PENERAPAN HYPNOBIRTHING DALAM MENURUNKAN TINGKAT KECEMASAN IBU HAMIL TRIMESTER TIGA MENJELANG PERSALINAN ANAK PERTAMA DI USIA DEWASA AWAL - Kamilia Asmarany (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2017)
Abstract The aim of this study is to find the influence of hypnobirthing method to decrease level’s of anxiety of early adult women’s confinement. The research was held in Ningsih Midwife’s from March until June 2012. This research used experimental research method which is kind of quasi experiment with one-group pre-posttest design. Analysis obtainded using the Wilcoxon test z = -3.061 , p = 0.002 < 0.05 (significant), meaning that there are significant differences in before and after hypnobirthing. From these results it was found that there are significant difference between groups of measurements before. Based on the results of this analysis, the hypothesis of this study is acceptable. This research’s hypothesis is hypnobirthing method effective to reduce anxiety in the first child labour in early adult mother. The implication of this research is hypnobirthing method can decrease the pregnant women’s level of anxiety towards confinement and easy to be executed. This method can be applied not only at midwife but also in pregnant women by her self.. Keywords: anxiety, hypnobirthing method, early adult mother